Identifikasi Pemahaman Konsep Usaha dan Energi Calon Guru Fisika - Muhammad Reyza Arief Taqwa (Pendidikan Kimia Unimus, 2019)
This study aims to reveal the students' conceptual understanding on the concept of work and energy. In this study focused on discussing the ability of students to understand the concept of kinetic energy. To achieve this goal, 5 reasoned multiple choice questions were used. The question is a standard test of basic physics lectures at UM. This research is a descriptive research. The study was conducted on 50 students in the